Correlation of Leg Length and Leg Muscle Strength on Leg Muscle Explosive Power of Men's Volleyball Student Activity Unit (UKM) Participants, PGRI Mahadewa University Indonesia - Budi Sudarsana, I Putu Agus (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study is a correlational study, because there is no relationship (correlation) between free variables and bound variables. The study population was the participants of the Student Activity Unit (SAU) of Putra Volleyball Universitas PGRI Mahadewa Indonesia, the total number of 39 people, while the technique used to take samples was by inclusion and exclusion techniques, namely: of the same sex, age ranges from 18-22 years, with good physical fitness, height 170-190 cm, body weight between 65-85 kg, and willing to participate in research. From the results of the data analysis, the value of the multiple correlation coefficient (R) =0.946 was obtained. This shows that there is a very strong correlation between limb length and limb muscle strength and limb muscle explosiveness of the participants of Student Activity Unit (SAU) of Putra Volleyball Universitas PGRI Mahadewa indonesia. From the calculation of the coefficient of determination or coefficient of determination (CD) is obtained KP= 89.49%. This means that the length of the limb and the strength of the limb muscles determine or determine by 89.49% the explosive power of the limb muscles of the participants of Student Activity Unit (SAU) Putra Volleyball Universitas PGRI Mahadewa indonesia, while the remaining 10.51% was determined by other factors not studied in this study. The F test calculation obtained an F-count value of 153.29 greater than the F-table of 3.26; so Ho was rejected and Ha was accepted (significant). Thus, it can be concluded that, there is a correlation of limb length and limb muscle strength to limb muscle explosiveness of participants of Student Activity Unit (SAU) of Putra Volleyball Universitas PGRI Mahadewa Indonesia.